Change-of-direction performance and its deficits in relation to countermovement-jump height and phase-specific performance among female athletes - Yamashita, N.; Sato, D.; Mishima, T. (International Journal of Sports Physiology and Performance, 2024)
Purpose Jump and linear sprint performances both correlate with pro-agility performance. However, correlation does not imply causation, and potential confounders may affect the correlation. Therefore, this study aimed to determine the relationship between change-of-direction (COD) performance and COD deficits (COD-D) in linear-sprint and countermovement-jump (CMJ) -related performance using multiple stepwise linear-regression models.